Feasibility study of uranium leaching from phosphate ore - D. Ghoddocy Nejad; M. Outokesh; A. Abdshahi; Kh. Khoshnoodi; A. Ghadiri; M. Akbari (مجله علوم و فنون هسته‌ای, 2023)
In this research, the uranium recovery from Zagros region phosphate ore by calcination and acid extraction technology has been investigated. Also, the effect of different parameters on calcination and dissolution of uranium was investigated. The results showed that calcination temperature and calcination time as calcination factors; Also, leaching temperature, dissolution time, ore particle size, acid concentration, and liquid-to-solid ratio are important factors in uranium recovery from ore. Optimum operating parameters were established as follows: calcination temperature: 900 °C, calcination time: 2h; leaching temperature: 80 °C, leaching time: 4h, particle size: smaller than 100 microns, the concentration of sulfuric acid: 4M and liquid to the solid ratio: 3/1 mL/g. Under these conditions, uranium extraction efficiency from phosphate ore of the Zagros region was 84%.